A gradient self-lubricating full ceramic retainer based on a three-period minimum surface configuration and a preparation method thereof

CN122943070APending Publication Date: 2026-10-20SHENYANG JIANZHU UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611094779.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

其一,现有的表面涂层或填料分散方案无法在陶瓷基体内部建立起三维贯通、体积占比充足且结构稳定的润滑剂储运网络,缺乏兼具高结构强度与持续自润滑供给能力的一体化陶瓷复合构型

Benefits of technology

1、本发明采用三周期最小表面隐式曲面作为多孔骨架的控制方程,该数学曲面在三维空间具有曲率的连续分布特征,不存在任何尖角或曲率突变点。相较于现有技术中因机械开槽或钻孔而在陶瓷基体中引入的尖锐棱角,本发明所述三周期最小表面拓扑构型的骨架与孔隙界面实现了应力流的平滑传递。当保持架在超高速旋转下承受巨大周向离心拉应力时,连续平滑的拓扑界面不会产生应力集中放大效应,从而显著降低了陶瓷材料因内部缺陷诱发脆性断裂的概率。同时,所述双连续交错互锁的两相体相结构使得陶瓷骨架与填充的固体润滑剂之间形成了三维空间内的相互机械锁合,这种空间约束增强了界面结合强度,在交变载荷与高速冲击工况下有效抑制了两相界面的脱粘与剥离。有利于提升保持架在交变载荷与高速冲击工况下的结构稳定性。此外,通过将基体孔隙率设置为径向功能梯度分布,有助于改善全陶瓷保持架在高速条件下的离心承载与脆性破坏问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a gradient self-lubricating ceramic cage based on a three-period minimum surface configuration and its preparation method, belonging to the field of ceramic bearing manufacturing technology. Existing ceramic cages often face the problem of sudden oil-deficient burning under extreme operating conditions. This invention integrates a solid lubricant into the ceramic matrix, constructing a double-continuous staggered interlocking skeleton with a three-period minimum surface configuration. Along the radial direction of the cage wall thickness, the porosity of the three-period minimum surface configuration exhibits a functional gradient change. The matrix is ​​radially divided from the outside to the inside into at least a porous friction zone for providing lubrication and a dense solid zone, exposing a two-phase coplanar mesh-like heterogeneous friction surface on the pocket friction contact surface. This invention utilizes the difference in the linear thermal expansion coefficients of the two phases to drive the solid lubricant to adaptively overflow and shear to form a film with temperature rise, achieving a synergistic function of strong load-bearing and active self-lubrication, effectively solving the problems of sudden breakage and lubrication deficiency under ultra-high-speed extreme operating conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic bearing manufacturing technology, and more particularly to a gradient self-lubricating all-ceramic cage based on a three-period minimum surface configuration and its preparation method. Background Technology

[0002] With the development of high-end equipment technology, the requirements for the limiting speed, load-bearing capacity, and high-temperature resistance of rolling bearings in their service environment have significantly increased, and traditional metal bearings can no longer meet the needs of extreme operating conditions. Ceramic bearings, with their high hardness, low density, and excellent high-temperature and corrosion resistance, have become key support components in high-end equipment fields such as aero-engines and precision machine tools. In the overall structure of a ceramic bearing, the cage serves as the core guiding and isolating component. Its function is to physically isolate adjacent rolling elements, preventing direct contact and adhesive wear between them during service, while simultaneously guiding the rolling elements to operate stably within the raceway.

[0003] Currently, industrial-grade ceramic bearing cages primarily utilize organic polymer materials such as polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE), or phenolic laminated fabric tubing (bakelite). These polymer materials possess excellent self-lubricating properties and flexible damping capabilities, effectively absorbing the minute vibrations and impacts generated during high-speed rolling element movement. However, the service environment of high-end equipment often involves intense frictional shearing and heat generation. These polymer materials have extremely low thermal conductivity and unstable thermal properties. Under the severe temperature rise caused by high-speed friction, they are prone to localized thermal degradation, severe dimensional creep, and thermal attenuation of mechanical strength, leading to nonlinear expansion and deformation of the cage and ultimately bearing seizure failure. Therefore, the adoption of all-ceramic self-lubricating cages has become an inevitable trend for improving the ultimate service life of ceramic bearings.

[0004] However, ceramic materials, as typical hard and brittle materials, possess excellent density and stable thermophysical and chemical properties, preventing material transfer at the friction pair surface, and their surfaces are completely non-absorbent of oil. Once external oil mist is blocked by ultra-high-speed air barriers under extreme operating conditions, the friction contact surface dries instantly, causing the coefficient of friction to surge to over 0.6, triggering intense frictional heat generation and leading to cage breakage due to thermal stress concentration. Therefore, ceramic cages are highly susceptible to the dual challenges of mechanical brittle fracture and lubrication loss during ultra-high-speed rotation.

[0005] To alleviate the problems of insufficient lubrication and centrifugal fracture at high speeds, existing patents mostly focus on optimizing the external macroscopic structure. Chinese invention patent CN1163366082A proposes a high-speed deep groove ball bearing cage with an oil reservoir structure. This improves grease flow by creating circumferential oil guide grooves and axial through holes between adjacent pockets, and carving cross-shaped arc-shaped oil reservoirs inside the pockets. Chinese invention patent CN110630639B proposes an asymmetrical split-type bearing cage with oil storage function. This design uses a boss at the upper end of the cage to scrape the fluid lubricant from the rolling element surface and forcibly collect and store it in a built-in macroscopic disc-shaped oil reservoir. However, these solutions all involve creating macroscopic holes and grooves in the ceramic material through machining. This slotted and hollowed-out design creates severe stress concentration at the edges of the holes and grooves under the huge circumferential centrifugal tensile stress field generated by ultra-high-speed rotation, becoming a preferred location for crack initiation and greatly increasing the risk of high-speed centrifugal fracture of the ceramic cage.

[0006] Furthermore, CN101400910A discloses a resin-based retainer for extremely low-temperature environments. The retainer body is constructed from super engineering plastics such as PEEK or PPS, incorporating solid lubricant materials (e.g., PTFE), and a recessed component made of a fluororesin composition is installed in the recessed portion. While this approach imparts a certain degree of self-lubrication to the retainer body through material composites, its matrix material remains a resin-based composite material. Essentially, it lacks the high rigidity and high-temperature dimensional stability of ceramic materials, failing to meet the stringent requirements of ultra-high-speed all-ceramic bearings for cage rigidity and thermal stability. Simultaneously, the solid lubricant in this approach is dispersed in the resin matrix as filler, lacking a continuous, interconnected lubricant supply channel, thus limiting the sustainability and reliability of its self-lubricating effect. CN1505494A discloses a polymer-metal composite cage for self-lubricating bearings, in which a porous metal layer (e.g., a silver layer) is chemically plated onto the surface of a polymer core, and then oil or grease is injected into the micropores of the porous metal layer. While this solution increases lubricant storage and retention capacity through a porous surface coating, the porous layer is only a thin layer covering the core surface and cannot provide a sufficient volume fraction of lubricant reserve to meet the continuous supply requirements under long-term extreme operating conditions. More importantly, this solution relies entirely on externally injected liquid lubricant (grease), and loses its self-lubricating ability once the external lubricant is depleted. Furthermore, the mechanical properties and thermal stability of its polymer core are far inferior to those of all-ceramic materials.

[0007] In summary, existing technologies still have the following fundamental shortcomings in resolving the contradiction between lubrication and breakage of ultra-high-speed ceramic cages: Firstly, existing surface coating or filler dispersion schemes cannot establish a three-dimensional, fully-volume, and structurally stable lubricant storage and transportation network within the ceramic matrix, and lack an integrated ceramic composite configuration that combines high structural strength with continuous self-lubricating supply capability.

[0008] Secondly, the lubricant release behavior in the existing solution is passive and uncontrollable. It continues to release even under low temperature or low load conditions, leading to premature depletion of the lubricant. In the event of sudden high temperature and high load conditions where lubrication is truly needed, it cannot achieve instantaneous response and targeted replenishment, lacking an adaptive and on-demand lubrication mechanism.

[0009] Third, porous ceramics prepared by traditional artificial pore opening or pore-forming agent methods have irregular pore morphology and poor curvature continuity, which can easily become stress concentration sources under service stress conditions, and cannot simultaneously achieve high porosity and high structural strength.

[0010] Therefore, there is an urgent need for a high-speed ceramic bearing cage that combines the high-speed tensile strength of the matrix with active self-lubrication capability to solve the problems of sudden breakage and lack of lubrication under ultra-high-speed extreme working conditions. Summary of the Invention

[0011] To address the aforementioned technical problems, a gradient self-lubricating ceramic cage based on a three-period minimum surface configuration and its preparation method are provided. This cage achieves adaptive and active lubricant supply while ensuring the overall structural strength of the cage through gradient design of a specific spatial topology and integrated composite of heterogeneous materials.

[0012] The technical means employed in this invention are as follows: A gradient self-lubricating all-ceramic cage based on a three-period minimum surface configuration includes a ceramic substrate with a circular thin-walled structure and multiple pockets uniformly distributed along the circumference of the substrate for accommodating rolling elements. The ceramic matrix has an integrally formed continuous porous skeleton inside, and the continuous porous skeleton has a three-period minimum surface topology. The internal space of the continuous porous skeleton is integrally filled with a solid lubricant, and the ceramic matrix and the solid lubricant form a three-dimensional interlocking structure through the spatial geometric constraints of the three-period minimum surface topology configuration. Along the radial wall thickness direction of the ceramic matrix, the porosity of the three-period minimum surface topology exhibits a continuous functional gradient change and a periodic axisymmetric distribution on the circumferential cross section. The solid lubricant and the ceramic matrix are exposed together on the friction contact surface of the pocket, forming a coplanar mesh-like heterogeneous structure.

[0013] Furthermore, along the radial wall thickness direction of the ceramic matrix from the outside to the inside, the ceramic matrix is ​​at least divided into a porous friction region for providing a self-lubricating material supply source and a dense solid region with zero porosity. The continuous, porous skeleton exists only within the porous friction zone and completely closes and disappears within the dense solid zone. The specific number of functional gradient regions and the porosity distribution curve of each region are determined by the number of three-period minimum surface topological space periodic units that can be accommodated along the radial wall thickness direction. When the number of periodic units is greater than or equal to six, a four-region gradient structure is adopted; when the number of periodic units is less than six, it is simplified to a two-region or three-region structure.

[0014] Furthermore, when the number of three-period minimum surface topological space periodic units that can be accommodated along the radial wall thickness direction is greater than or equal to six, the porous friction region is subdivided radially from the outside to the inside into an outer ring transition region, a core friction region, and an inner ring transition region, and the ceramic matrix is ​​radially from the outside to the inside into an outer ring transition region, a core friction region, an inner ring transition region, and a dense solid region. The radial position is defined as the percentage of the radial depth from the outermost surface of the ceramic substrate to the total radial wall thickness of the substrate. The outer ring transition zone is located in the range of 0% to 35% of the radial depth. The initial porosity of this zone is set to a value between 15% and 25%, and the initial porosity increases continuously and nonlinearly in the radial direction until it reaches the constant porosity value of the core friction zone. The core friction zone is located within a radial depth range of 35%-55%, and the porosity of this zone remains at a constant value between 35% and 55%. The inner ring transition zone is located in the radial depth range of 55% to 65%. The porosity of this zone decreases continuously and non-linearly from the constant porosity value of the core friction zone in the radial direction until it drops to a certain value between 15% and 25%. It further decreases continuously to zero porosity at the boundary with the dense solid zone. The dense solid region is located within a radial depth range of 65% to 100%, and the porosity of this region is always 0. The three-period minimum surface topology is completely closed within this region. The ceramic material in the dense solid region remains in a completely dense state to bear the circumferential centrifugal tensile stress generated under high-speed rotation.

[0015] Furthermore, the average channel diameter of the three-period minimum surface topology configuration in the continuously permeable porous skeleton is 150~350μm.

[0016] Furthermore, the mathematical surface of the three-period minimum surface topology is selected from at least one implicit surface function among the Gyroid surface, Primitive surface, Diamond surface or I-WP surface, and the implicit surface function has a continuous curvature distribution and a smooth transition feature without self-intersection in three-dimensional space.

[0017] Furthermore, the linear thermal expansion coefficient of the solid lubricant, which is compositely filled inside the continuous porous skeleton, is higher than that of the ceramic matrix. The difference in their linear thermal expansion coefficients is one to two orders of magnitude, so as to achieve the supply of adaptive lubricating material driven by differential expansion based on temperature field changes.

[0018] Furthermore, the ceramic matrix is ​​made of any one of silicon nitride ceramics, zirconium oxide ceramics, or silicon carbide ceramics; The solid lubricant is selected from at least one polymer material selected from polytetrafluoroethylene, polyetheretherketone, or polyimide.

[0019] On the other hand, the present invention also discloses a method for manufacturing the above-mentioned ceramic cage, comprising the following steps: Step 1: Construct a digital model of the ceramic cage based on the three-period minimum surface implicit surface control equation with radial functional gradient porosity distribution characteristics, and reserve machining allowances for the outer cylindrical surface, inner cylindrical surface, and vertical inner wall of the pocket that require subsequent precision machining in the digital model; then, use ceramic photopolymerization 3D printing technology to stack and solidify the ceramic cage blank with radial functional gradient porosity characteristics layer by layer by controlling the layer-by-layer exposure energy and curing layer thickness. Step 2: The ceramic cage blank is placed in a debinding furnace for a multi-stage slow heating controlled step-by-step hot debinding treatment to remove the organic binder inside the blank; then the debinding blank is transferred to a high-temperature sintering furnace for densification sintering treatment to obtain a three-cycle minimum surface ceramic cage skeleton blank with a three-dimensional rigid porous network. Step 3: Using a fluid abrasive flow processing technology containing fine diamond abrasive particles, the abrasive suspension is pressurized and pushed into the porous through-flow channel of the skeleton blank, so that the abrasive suspension flows through the entire three-dimensional continuous through-flow porous network and is discharged from the outlet side. The microscopic step effect and free powder adhering to the inner wall of the channel are removed by alternating forward and reverse circulation flushing. Step 4: The skeleton blank after fluid abrasive flow treatment is placed in a vacuum impregnation chamber and evacuated to an absolute negative pressure range of 10~100Pa to remove residual air and adsorbed impurities inside the three-dimensional continuous porous network. Then, under the condition of maintaining the vacuum state, a liquid, molten or suspended solid lubricant precursor is introduced to completely immerse the skeleton blank. High-pressure gas is then introduced into the impregnation chamber to establish a positive pressure environment of 1.5~3.5MPa. Under the positive pressure, the solid lubricant precursor is forced into the internal space of the entire continuous porous skeleton. Then, in-situ solidification or cooling crystallization treatment is performed to make the volume filling density of the solid lubricant inside the porous skeleton reach 85%~95%, thus obtaining a ceramic-solid lubricant dual continuous heterogeneous composite cage blank. Step 5: Use a diamond grinding tool to perform precision mechanical grinding on the outer cylindrical surface, inner cylindrical surface, and vertical inner wall of the pocket of the composite cage blank. Remove the mechanical grinding allowance reserved in Step 1 and remove the residual solid lubricant residue on the surface. This will enable the cage to meet the predetermined mechanical dimensional accuracy and geometric tolerance requirements, and simultaneously expose the grid-like heterogeneous structure of the ceramic matrix and the solid lubricant on the friction contact surface of the pocket.

[0020] Furthermore, the ceramic slurry used in the ceramic photopolymerization 3D printing forming technology in step 1 is prepared by mixing photosensitive resin, dispersant, surface modifier and ceramic micro powder, and the volume solid content of the ceramic micro powder is 45%~55%.

[0021] Furthermore, the fluid abrasive flow processing technology in step 3 achieves graded and controllable improvement of the surface quality of the internal channels of the three-cycle minimum surface topology by programmatically adjusting the extrusion pressure of the abrasive suspension, the average particle size of the diamond abrasive, and the number of alternating forward and reverse cyclic scouring.

[0022] Compared with the prior art, the present invention has the following advantages: 1. This invention employs a three-period minimum surface implicit curve as the governing equation for the porous skeleton. This mathematical surface exhibits a continuous curvature distribution in three-dimensional space, without any sharp corners or abrupt curvature changes. Compared to the sharp edges introduced into the ceramic matrix by mechanical grooving or drilling in existing technologies, the skeleton and pore interface of the three-period minimum surface topology configuration described in this invention achieves smooth stress flow transmission. When the cage is subjected to enormous circumferential centrifugal tensile stress under ultra-high-speed rotation, the continuous and smooth topological interface does not produce a stress concentration amplification effect, thus significantly reducing the probability of brittle fracture induced by internal defects in the ceramic material. Simultaneously, the dual-continuous interlocking two-phase bulk structure creates a three-dimensional mechanical interlock between the ceramic skeleton and the filled solid lubricant. This spatial constraint enhances the interfacial bonding strength, effectively suppressing debonding and peeling of the two-phase interface under alternating loads and high-speed impact conditions. This is beneficial for improving the structural stability of the cage under alternating loads and high-speed impact conditions. Furthermore, by setting the matrix porosity to a radial functional gradient distribution, it helps to improve the centrifugal load and brittle fracture problem of all-ceramic cages under high-speed conditions.

[0023] 2. This invention employs a functional gradient design of the minimum surface porosity of the three-cycle configuration along the radial direction. A high-porosity porous friction zone is established on the outer side of the matrix to provide ample lubricant storage and supply channels, while a completely dense solid region is retained in the high-stress zone near the inner ring to bear the majority of the centrifugal tensile stress. In conventional technologies, uniform porous structures suffer from insufficient strength if the porosity is too high, and limited lubricant storage if the porosity is too low. This invention achieves an optimized spatial combination of the lubricant supply function of the high-porosity region and the high-stiffness load-bearing function of the dense solid region within the same component through a four-zone gradient matching of the outer ring transition zone, the core friction zone, the inner ring transition zone, and the solid region. This results in abundant self-lubricating capability without sacrificing structural strength.

[0024] 3. This invention utilizes the order-of-magnitude difference in the linear thermal expansion coefficients between the solid lubricant filled within the porous framework and the ceramic matrix to construct a unique differential expansion-driven release mechanism. When the bearing encounters sudden operating conditions such as transient oil cut-off or high-load friction, causing a sharp rise in the contact surface temperature, the polymeric solid lubricant embedded within the three-period minimum surface framework undergoes volume expansion due to anisotropic thermal excitation. Because the expansion amount is significantly greater than that of the rigid ceramic framework, the polymeric phase is forced out from within the framework along the three-dimensional interconnected pores and reaches the friction surface. Under the alternating shear action of the rolling elements, the overflowing lubricant spreads in situ at the contact interface, forming a continuous low-shear strength transfer film. This transforms the original ceramic-to-ceramic hard contact into low-shear tearing between polymer chains within the lubricating film, instantly reducing the coefficient of friction from above 0.6 to below 0.08. When the operating conditions return to normal and the temperature drops, the volume contraction of the polymeric phase slows down or even stops the overflow process, thereby avoiding excessive and ineffective loss of lubricant. This adaptive control mechanism is completely absent in existing technologies. It enables the cage of this invention to maintain a reserve of solid lubricant without consumption when external liquid lubrication is in normal supply, and to automatically release lubricant to implement emergency protection in the critical moment of sudden oil cut-off, which greatly improves the survivability of the bearing system under extreme working conditions.

[0025] 4. In the process scheme of this invention, ceramic photopolymerization 3D printing technology enables the integrated forming of a three-cycle minimum surface porous skeleton with continuous curvature characteristics inside the ceramic matrix; fluid abrasive flow process solves the adverse effects of micro-defects on the internal flow channel unobstructedness and structural fatigue life of additive manufacturing surface; vacuum positive pressure alternating impregnation technology ensures the full and dense filling of polymer lubricant inside the micro-fine three-dimensional interconnected network.

[0026] 5. This invention utilizes the difference in linear thermal expansion coefficients between the solid lubricant and the ceramic matrix to form a transient adaptive lubrication mechanism based on temperature field changes. When transient high-load or high-speed conditions cause the friction surface temperature to rise, the solid lubricant filling the skeleton phase undergoes microscopic volume expansion and overflows towards the friction interface. Under the alternating shear action of the rolling elements, the overflowing lubricant phase rapidly spreads, adheres, and forms a continuous microscopic solid lubricant transfer film on the friction contact surface, thereby transforming the direct contact between the ceramic and the rolling elements into low-shear tearing within the lubricant film, providing immediate replenishment lubrication and wear protection. After the operating conditions recover and the temperature decreases, the solid lubricant overflows at a slower pace or stops, thus avoiding excessive consumption of the lubricant phase. This invention is applicable to all-ceramic bearings, providing steady-state emergency self-lubricating support under extreme operating conditions for aero-engine spindle bearings, precision machine tool spindles, and high-speed support systems in extreme service environments such as high vacuum and strong corrosion. This is fundamentally different from existing technologies that rely solely on surface coatings or discrete filler particles to provide limited lubrication supply. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a schematic diagram of the ceramic cage in an example of the present invention.

[0029] Figure 2 This is a schematic diagram of a ceramic retainer with a Gyroid configuration in an example of the present invention.

[0030] Figure 3 This is a schematic diagram of the Gyroid configuration in an example of the present invention.

[0031] Figure 4 This is a schematic diagram of the radial gradient distribution of the ceramic cage in an example of the present invention.

[0032] Figure 5 This is a flowchart illustrating the preparation steps of the gradient self-lubricating ceramic cage in an example of the present invention.

[0033] Among them, 1. ceramic cage substrate; 2. pocket; 3. porous skeleton; 4. mesh-like heterogeneous structure. Detailed Implementation

[0034] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0037] Unless otherwise specifically stated, the relative arrangement, numerical expressions, and values ​​of the components and steps described in these embodiments do not limit the scope of the invention. It should also be understood that, for ease of description, the dimensions of the various parts shown in the drawings are not drawn to actual scale. Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters in the following figures denote similar items; therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0038] In the description of this invention, it should be understood that the orientation or positional relationship indicated by directional terms such as "front, back, up, down, left, right", "horizontal, vertical, horizontal" and "top, bottom" is generally based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing this invention and simplifying the description. Unless otherwise stated, these directional terms do not indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on the scope of protection of this invention. The directional terms "inner" and "outer" refer to the inner and outer contours relative to the outline of each component itself.

[0039] For ease of description, spatial relative terms such as "above," "on top of," "on the upper surface of," "above," etc., are used herein to describe the spatial positional relationship of a device or feature as shown in the figures to other devices or features. It should be understood that spatial relative terms are intended to encompass different orientations in use or operation beyond the orientation of the device as described in the figures. For example, if the device in the figures were inverted, a device described as "above" or "on top of" other devices or structures would subsequently be positioned as "below" or "under" other devices or structures. Thus, the exemplary term "above" can include both "above" and "below." The device may also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used herein will be interpreted accordingly.

[0040] Furthermore, it should be noted that the use of terms such as "first" and "second" to define components is merely for the purpose of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention.

[0041] like Figure 1 and Figure 2 As shown, this invention discloses a gradient self-lubricating all-ceramic cage based on a three-period minimum surface configuration, comprising a ceramic substrate 1 with a circular thin-walled structure and multiple pockets 2 uniformly distributed along the circumference of the substrate for accommodating rolling elements. The ceramic substrate 1 has an integrally formed continuous porous skeleton 3 with a three-period minimum surface topology. A solid lubricant is integrally filled in the internal space of the continuous porous skeleton 3, and the ceramic substrate 1 and the solid lubricant form a three-dimensional interlocking structure through the spatial geometric constraints of the three-period minimum surface topology. Through the mathematical curvature continuity of the topology and the three-dimensional spatial interlocking within the ceramic and polymer phases, the local stress concentration caused by traditional mechanical grooving can be effectively alleviated, and the interfacial constraint force between the two phases can be enhanced.

[0042] In this embodiment, along the radial wall thickness direction of the ceramic substrate 1, the porosity of the three-period minimum surface topology exhibits a continuous functional gradient change and a periodic axisymmetric distribution on the circumferential cross-section. The solid lubricant and the ceramic substrate 1 are exposed together on the friction contact surface of the pocket 2, forming a coplanar mesh-like heterostructure 4. Under the shearing action of the rolling element, this mesh-like heterostructure 4 can form a continuous solid lubricant transfer film in situ at the friction interface, thereby avoiding direct contact between the ceramics and achieving instantaneous replenishment lubrication under extreme operating conditions.

[0043] Furthermore, to ensure the overall structural strength of the cage, the ceramic substrate 1 is divided, from the outside to the inside, along the radial wall thickness direction, into at least a porous friction zone for providing a self-lubricating material supply source and a dense solid zone D with zero porosity. The continuously permeable porous skeleton 3 exists only within the porous friction zone and completely closes and disappears within the dense solid zone D. In this embodiment, the specific number of functional gradient regions and the porosity distribution curve of each region are determined by the number of three-period minimum surface topological space periodic units that can be accommodated along the radial wall thickness direction. A four-zone gradient structure is adopted when the number of periodic units is greater than or equal to six.

[0044] Specifically, in this embodiment, when the number of three-cycle minimum surface topological space periodic units that can be accommodated along the radial wall thickness direction is greater than or equal to six, the porous friction zone is subdivided radially from the outside to the inside into an outer ring transition zone A, a core friction zone B, and an inner ring transition zone C. That is, the ceramic substrate is radially from the outside to the inside into an outer ring transition zone A, a core friction zone B, an inner ring transition zone C, and a dense solid zone D. The radial position is defined as the percentage of the radial depth from the outermost surface of the ceramic substrate 1 to the total radial wall thickness of the substrate: the outer ring transition zone A is located in the radial depth range of 0% to 35%, and the initial porosity of this region is set to a value between 15% and 25%, and the initial porosity increases continuously and non-linearly in the radial inward direction until it reaches the constant porosity value of the core friction zone B. The core friction zone B is located in the radial depth range of 35% to 55%, and the porosity of this region remains a constant value between 35% and 55%. The inner transition zone C is located within a radial depth of 55% to 65%. The porosity of this zone continuously and non-linearly decreases radially inward from the constant porosity value of the core friction zone B until it reaches a value between 15% and 25%, and further decreases continuously to zero porosity at the boundary with the dense solid zone D. The dense solid zone D is located within a radial depth of 65% to 100%. The porosity of this zone is always zero. The three-period minimum surface topology is completely closed within this zone. The ceramic material of the dense solid zone D remains completely dense to withstand the circumferential centrifugal tensile stress generated under high-speed rotation, preventing the cage from centrifugal bursting failure. As another feasible implementation, when the number of porous topological space periodic units that can be accommodated along the radial direction is less than 6, the functional gradient change can be simplified to a two-zone or three-zone structure.

[0045] Preferably, in this embodiment, the average channel diameter of the three-period minimum surface topology configuration in the continuous through porous skeleton 3 is 150~350 μm. Its spatial scale can prevent the polymer solid lubricant from generating excessive flow resistance when the precursor is filled, and can also provide sufficient curved surface contact area.

[0046] Furthermore, the mathematical surface of the three-period minimum surface topology is selected from at least one implicit surface function among the Gyroid surface, Primitive surface, Diamond surface or I-WP surface. The implicit surface function has a continuous curvature distribution and a smooth transition without self-intersection in three-dimensional space, which can effectively reduce the stress concentration inside the porous skeleton 3.

[0047] In this embodiment, the linear thermal expansion coefficient of the solid lubricant composite-filled within the continuous porous skeleton 3 is higher than that of the ceramic matrix 1, with a difference of one to two orders of magnitude. This enables the supply of adaptive lubricating material driven by differential expansion based on temperature field changes. The principle is that when transient high load or high-speed conditions cause a rise in the friction surface temperature, the solid lubricant filled within the skeleton bulk phase undergoes microscopic volume expansion and overflows towards the friction interface. Under the alternating shear action of the rolling element, the overflowing lubricating phase rapidly spreads, adheres, and forms a continuous microscopic solid lubricant transfer film on the friction contact surface. This transforms the direct contact between the ceramic and the rolling element into low-shear tearing within the lubricating film, providing immediate replenishment lubrication and wear protection. After the operating conditions recover and the temperature decreases, the solid lubricant overflows slowly or stops, thus avoiding excessive consumption of the lubricating phase.

[0048] In a preferred embodiment of the present invention, the ceramic matrix 1 is made of any one of silicon nitride ceramics, zirconium oxide ceramics, or silicon carbide ceramics; the solid lubricant is made of at least one polymer material selected from polytetrafluoroethylene, polyetheretherketone, or polyimide.

[0049] On the other hand, the present invention also discloses a method for preparing the above-mentioned ceramic retainer, such as... Figure 5 The flowchart shown includes the following steps: Step 1: Construct a digital model of the ceramic cage based on the three-period minimum implicit surface control equation with radial functional gradient porosity distribution characteristics. Reserve machining allowances for the outer cylindrical surface, inner cylindrical surface, and vertical inner wall of the pocket requiring subsequent precision machining in the digital model. Then, using ceramic photopolymerization 3D printing technology, by controlling the layer-by-layer exposure energy and cured layer thickness, a ceramic cage blank with radial functional gradient porosity characteristics is formed by layer-by-layer deposition and curing. Preferably, the ceramic slurry used is prepared by mixing photosensitive resin, dispersant, surface modifier, and ceramic micropowder, wherein the volume solid content of the ceramic micropowder is 45%~55%.

[0050] Step 2: The ceramic cage blank is placed in a debinding furnace for a multi-stage slow-heating step-by-step thermal debinding treatment to remove the organic binder inside the blank and avoid micro-cracks caused by rapid gas release; then the debinded blank is transferred to a high-temperature sintering furnace for densification sintering treatment to obtain a three-dimensional rigid porous network with a three-cycle minimum surface ceramic cage skeleton blank.

[0051] Step 3 employs a fluid abrasive flow machining process containing fine diamond abrasive grains. The abrasive suspension is pressurized and pushed into the porous, interconnected channels of the skeleton blank through the entire three-dimensional continuous porous network and discharged from the outlet. This process removes the microscopic step effect remaining after layer-by-layer curing in 3D printing and the free powder adhering to the channel walls through alternating forward and reverse cyclic flushing. In this embodiment, this step achieves graded and controllable improvement of the surface quality of the channels within the three-period minimum surface topology by programmatically adjusting the extrusion pressure of the abrasive suspension, the average particle size of the diamond abrasive grains, and the number of alternating forward and reverse cyclic flushing cycles. This prevents pore blockage and ensures the continuity of subsequent solid lubricant impregnation.

[0052] Step 4: The skeleton blank after fluid abrasive flow treatment is placed in a vacuum impregnation chamber and evacuated to an absolute negative pressure range of 10~100Pa to remove residual air and adsorbed impurities inside the three-dimensional continuous porous network. Then, under the condition of maintaining the vacuum state, a solid lubricant precursor in liquid, molten or suspension state is introduced to completely immerse the skeleton blank. High-pressure gas is then introduced into the impregnation chamber to establish a positive pressure environment of 1.5~3.5 MPa. Under the positive pressure, the solid lubricant precursor overcomes the capillary resistance of the ceramic wall and is forced into the entire internal space of the continuous porous skeleton 3. Then, in-situ solidification or cooling crystallization treatment is performed to make the volume filling density of the solid lubricant inside the porous skeleton 3 reach 85%~95%, and a ceramic-solid lubricant dual continuous heterogeneous composite cage blank is obtained.

[0053] Step 5: Using a diamond grinding wheel as the grinding tool, precision mechanical grinding is performed on the outer cylindrical surface, inner cylindrical surface, and vertical inner wall of the pocket 2 of the composite cage blank. This removes the machining allowance reserved in Step 1 and cleans away any residual solid lubricant residue on the surface, ensuring the cage meets the predetermined dimensional accuracy and geometric tolerance requirements. Simultaneously, the mesh-like heterogeneous structure 4, coplanar between the ceramic substrate 1 and the solid lubricant, is exposed on the friction contact surface of the pocket 2. Under the action of the grinding force, the mesh-like heterogeneous structure 4, coplanar between the ceramic substrate 1 and the solid lubricant, is exposed on the friction contact surface of the pocket 2. Under the frictional shearing action of the rolling elements, the solid lubricant is coated in situ and forms a uniform and stable transfer film.

[0054] Example 1 This embodiment uses the ceramic cage of a 7008C angular contact ball bearing as the specific implementation and verification object. In this embodiment, the ceramic matrix 1 is made of zirconia ceramic, and the solid lubricant is a polyimide (PI) polymer. The radial total wall thickness of the cage matrix 1 is designed to be 2.7 mm.

[0055] In this embodiment, the mathematical surface of the continuously permeable porous framework 3 is digitally reconstructed and its gradient porosity modulated using the Gyroid (G-surface) implicit surface function control equation. The mathematical equation is expressed as follows:

[0056] when F ( x , y , z )≤ t When is defined as the zirconium oxide ceramic matrix phase in this embodiment, when F ( x , y , z )> t This is defined as the phase where solid lubricant fills the pores. By controlling... t The expression function can realize the functional gradient distribution of porosity along the radial (wall thickness) direction of the cage. This embodiment introduces a radial wall thickness depth variable. u Its spatial function expression is defined as:

[0057] In the formula, R out To maintain the outer radius of the frame, in this embodiment... R out =29.45 mm; (x 2 +y 2 ) 1 / 2 This represents the radial distance from the current spatial point to the center axis of the cage. The radial wall thickness depth variable... u ∈[0, 2.7 mm], where u =0 corresponds to the outermost surface of the cage substrate. u =2.7 mm corresponds to the innermost surface of the cage base.

[0058] Since the number of periodic units that can be accommodated in the radial direction of the cage in this embodiment is less than 6, a dual-zone structure is adopted. That is, the substrate 1 is divided into a porous friction zone A and a solid zone B with a porosity of 0 and a completely closed topological configuration in the radial direction from the outside to the inside.

[0059] By establishing parameters t Radial wall thickness depth variableu Piecewise function relationship t ( u This allows for the construction of a continuous, interconnected porous framework 3 with a radial functional gradient distribution. Within a 2.7 mm wall thickness segment along the radial direction of the substrate 1 from the outside in, each region... t ( u The specific parameter settings are as follows: The porous friction zone A is located at a radial depth u Within the range [0, 1.755 mm] (corresponding to a wall thickness percentage of 0%-65%), the parameters within this range... t ( u ) Remain at a constant value, that is:

[0060] At this point, the local porosity inside the corresponding porous friction zone is about 50%, and the average channel diameter inside the porous skeleton 3 is about 220 μm, which is used to provide an abundant and stable oil storage and self-lubricating source.

[0061] Solid region B is located at a radial depth u Within the range of [1.755 mm, 2.7 mm] (corresponding to a wall thickness percentage of 65%-100%). Parameters within this region... t ( u ) Remain at a constant value, that is:

[0062] At this point, the region is completely closed to form a 0.945 mm thick zirconia solid, which is used to resist the maximum circumferential tensile stress of the cage under ultra-high speed centrifugal conditions.

[0063] In this embodiment, the linear thermal expansion coefficient of the selected zirconia ceramic substrate 1 is approximately 1.05 × 10⁻⁶. -5 K, while the linear thermal expansion coefficient of the composite-filled polyimide solid lubricant is approximately 4.5 × 10⁻⁶. -5 K. The linear thermal expansion coefficient of the polymer phase is more than one order of magnitude higher than that of the ceramic skeleton, thereby establishing a basis for adaptive lubrication extrusion kinetics driven by the temperature field within the bulk phase.

[0064] In this embodiment, as Figure 5 As shown, the gradient self-lubricating zirconia ceramic cage based on the three-period minimum surface configuration was prepared by the following method: Step 1: 3D printing to form the shape Based on the gradient Gyroid control equations set above and t ( u ) Parametric piecewise functions are used to establish a digital model of the cage, such as Figure 2As shown, the model size is proportionally enlarged and compensated according to the sintering shrinkage rate, and a precision grinding allowance of 0.30 mm is uniformly reserved for the inner and outer cylindrical surfaces and the inner wall of the pocket 2.

[0065] A high-solids-content photocurable zirconia ceramic slurry was prepared by mixing pretreated high-purity zirconia powder (with a median particle size of 0.5 μm and a volume solids content of 52 vol%) with an acrylic photosensitive resin, a polyurethane dispersant, and a photoinitiator in a premix. The mixture was then dispersed by high-speed ball milling in a planetary mixer for 6 hours, followed by degassing under reduced pressure. The prepared slurry was poured into a ceramic photocurable 3D printer, and the layer thickness was set to 25 μm. Layer-by-layer curing was performed using a UV laser to print a ceramic cage preform with radially functionally graded porosity.

[0066] Step 2: Degreasing and Sintering The printed preform is placed in a two-phase flow adhesive oven for thermal debinding. To prevent the high-solids resin matrix from undergoing violent vaporization at high temperatures, which could lead to cracks or collapse of the microporous skeleton 3, a stepped debinding process with multi-stage slow heating control is adopted.

[0067] The temperature was increased from room temperature to 250 ℃ at an extremely low rate of 0.1 ℃ / min and held for 2 hours; then increased to 450 ℃ at 0.2 ℃ / min and held for 4 hours to allow the macromolecular resin chains to fully decompose and slowly discharge; finally, the temperature was increased to 600 ℃ at 0.5 ℃ / min and held for 2 hours to complete the glue discharge.

[0068] Subsequently, the degreased green body was transferred to a high-temperature sintering furnace for high-temperature solid-state sintering in an air atmosphere. The temperature was raised to 1480 ℃ and held for 3 hours to drive the zirconia nanoparticles to undergo grain boundary diffusion, reorganization, and phase densification reconstruction. After cooling, a zirconia ceramic cage skeleton green body with a three-dimensional rigid porous network on the Gyroid surface was obtained.

[0069] Step 3: Fluid Abrasive Flow Treatment Because photopolymer 3D printing has a step effect of layer-by-layer exposure, and trace amounts of unreacted powder may remain in the internal microchannels after sintering, this step involves loading the sintered skeleton blank into a special fluid abrasive flow fixture to prepare an abrasive suspension using diamond microparticles with a particle size of 3 μm as abrasives and a high-viscosity polymer liquid as a carrier.

[0070] The fluid abrasive flow device is started, and the pressurization thrust is set to 3.5 MPa. The abrasive suspension is controlled to be forced into the outer ring surface, flow through the interior of the continuous porous framework 3, and exit from the other end, continuously alternating between forward and reverse cycles for 150 times. Utilizing the micro-shearing action of fine abrasive particles on the penetrating three-dimensional curved wall, the micro-defects and free powder on the inner wall of the channel are thoroughly removed, reducing the surface roughness of the internal channel to a minimum.R a Below 0.15 μm, ensure the continuity of subsequent polymer filling and eliminate stress concentration sharp corners.

[0071] Step 4: Lubricant filling The zirconia skeleton blank after cleaning and polishing is placed in the fixture of the vacuum impregnation chamber. The vacuum pump is started to evacuate to an absolute negative pressure of 30 Pa, and then heated at 120 ℃ for 1 hour to completely remove the residual air, water vapor and adsorbed trace impurities buried deep inside the Gyroid porous microchannel.

[0072] While maintaining a vacuum, a liquid soluble polyamic acid precursor solution (a polyimide precursor with a solid content of 35 wt%, diluted in NMP solvent) was introduced into the impregnation chamber and completely immersed the retainer. The vacuum was then disengaged, and high-pressure nitrogen gas was introduced into the impregnation chamber to rapidly establish a positive pressure environment of 2.5 MPa. Under this forced positive pressure, the fluid overcame the capillary viscous resistance of the zirconia porous wall and was forcibly forced into the entire microchannel of the permeable porous framework 3 within 30 minutes.

[0073] After pressing, the cage is removed and placed in an oven for segmented thermosetting imidization: first, the solvent is removed at 80 °C, then the temperature is increased to 150 °C at a rate of 1 °C / min and held for 1 hour, then increased to 250 °C and held for 2 hours, and finally the in-situ thermocyclization reaction (imidization) is completed at 350 °C, so that the polyamic acid is completely converted into a high-molecular-weight polyimide solid lubricant. The solid lubricant achieves a volume filling density of 90% in the internal through-pores, resulting in a zirconia-polyimide bicontinuous space-interlocked composite cage preform.

[0074] Step 5: Precision Machining The composite cage blank is fixed on a high-speed precision cylindrical grinder and a multi-axis CNC machine tool. Diamond grinding wheels are used to grind the outer and inner cylindrical surfaces respectively, removing a machining allowance of 0.30 mm to ensure that the cage's external dimensions and form and position tolerances meet the P4 grade bearing matching standard.

[0075] Subsequently, a diamond grinding head was used to grind the vertical inner wall of the circular pocket 2 to remove the excess polymer floating adhesive layer on the surface. The friction contact surface of the pocket 2 was exposed to reveal a grid-like heterostructure 4 consisting of a dense zirconium oxide skeleton and a polyimide solid lubricant that are interwoven and coplanar. The two phase interfaces are flush and the boundaries are clear.

[0076] The cage in this embodiment can be applied to extreme operating conditions such as transient oil starvation / oil cut-off in ultra-high-speed ceramic bearings or aero-engine spindles. When the cage is subjected to huge centrifugal tensile stress, the solid region B, which accounts for 35% of the wall thickness, plays a high-rigidity supporting role and bears the main circumferential centrifugal tensile stress. When the ceramic bearing is under oil cut-off or transient high-load conditions, the high-frequency collision friction between the rolling elements and the vertical inner wall of the pocket 2 causes the contact surface temperature to rise sharply. At this time, the polyimide solid lubricant 4 in the porous friction region A is excited by the temperature rise and undergoes microscopic thermal motion. Due to its linear thermal expansion coefficient (4.5×10⁻⁶), the polyimide solid lubricant 4 undergoes microscopic thermal motion. -5 K) was significantly higher than that of the zirconia framework (1.05 × 10⁻⁶). -5 Constrained by the three-dimensional anisotropic structure of the rigid ceramic wall, the expanded polymer phase is extruded along the mesh-like heterostructure 4 of the pocket 2 and overflows onto the surface. The polyimide actively overflowing to the friction interface undergoes rapid physical adhesion and chemical adsorption on the contact trajectory surface of the pocket 2 under the high-speed alternating shear and rolling action of the rolling element, spreading in situ to form a uniform and dense microscopic solid lubricant transfer film. This transfer film directly transforms the strong frictional shear between the rolling element and the ceramic matrix into low-shear tearing of low-molecular bonds within the lubricant film, instantly reducing the coefficient of friction to below 0.08, effectively blocking thermal and adhesive wear of the ceramic matrix. When the operating conditions recover and the temperature decreases, the volume of both phases shrinks back, and the polymer solid lubricant stops overflowing, thus avoiding excessive and ineffective consumption of the lubricating phase and achieving steady-state emergency self-lubrication support under extreme operating conditions.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A gradient self-lubricating all-ceramic cage based on a three-period minimum surface configuration, characterized in that, It includes a ceramic matrix with a thin-walled annular structure and multiple pockets evenly distributed along the circumference of the matrix for accommodating rolling elements. The ceramic matrix has an integrally formed continuous porous skeleton inside, and the continuous porous skeleton has a three-period minimum surface topology. The internal space of the continuous porous skeleton is integrally filled with a solid lubricant, and the ceramic matrix and the solid lubricant form a three-dimensional interlocking structure through the spatial geometric constraints of the three-period minimum surface topology configuration. Along the radial wall thickness direction of the ceramic matrix, the porosity of the three-period minimum surface topology exhibits a continuous functional gradient change and a periodic axisymmetric distribution on the circumferential cross section. The solid lubricant and the ceramic matrix are exposed together on the friction contact surface of the pocket, forming a coplanar mesh-like heterogeneous structure.

2. The ceramic retainer according to claim 1, characterized in that: Along the radial wall thickness direction of the ceramic matrix from the outside to the inside, the ceramic matrix is ​​at least divided into a porous friction zone for providing a self-lubricating material supply source and a dense solid zone with zero porosity. The continuous, through-hole porous skeleton exists only within the porous friction zone and completely closes and disappears within the dense solid zone. The specific number of functional gradient regions and the porosity distribution curve of each region are determined by the number of three-period minimum surface topological space periodic units that can be accommodated along the radial wall thickness direction. When the number of periodic units is greater than or equal to six, a four-region gradient structure is adopted; when the number of periodic units is less than six, it is simplified to a two-region or three-region structure.

3. The ceramic retainer according to claim 2, characterized in that, When the number of three-period minimum surface topological space periodic units that can be accommodated along the radial wall thickness direction is greater than or equal to six, the porous friction region is subdivided radially from the outside to the inside into an outer ring transition region, a core friction region, and an inner ring transition region, and the ceramic matrix is ​​radially from the outside to the inside into an outer ring transition region, a core friction region, an inner ring transition region, and a dense solid region. The radial position is defined as the percentage of the radial depth from the outermost surface of the ceramic substrate to the total radial wall thickness of the substrate. The outer ring transition zone is located in the range of 0% to 35% of the radial depth. The initial porosity of this zone is set to a value between 15% and 25%, and the initial porosity increases continuously and nonlinearly in the radial direction until it reaches the constant porosity value of the core friction zone. The core friction zone is located within a radial depth range of 35%-55%, and the porosity of this zone remains at a constant value between 35% and 55%. The inner ring transition zone is located in the radial depth range of 55% to 65%. The porosity of this zone decreases continuously and non-linearly from the constant porosity value of the core friction zone in the radial direction until it drops to a certain value between 15% and 25%. It further decreases continuously to zero porosity at the boundary with the dense solid zone. The dense solid region is located within a radial depth range of 65% to 100%, and the porosity of this region is always 0. The three-period minimum surface topology is completely closed within this region. The ceramic material in the dense solid region remains in a completely dense state to bear the circumferential centrifugal tensile stress generated under high-speed rotation.

4. The ceramic retainer according to claim 1, characterized in that: The average channel diameter of the three-period minimum surface topology configuration in the continuously permeable porous framework is 150~350μm.

5. The ceramic retainer according to claim 1, characterized in that: The mathematical surface of the three-period minimum surface topology is selected from at least one implicit surface function among the Gyroid surface, Primitive surface, Diamond surface or I-WP surface, and the implicit surface function has a continuous curvature distribution and a smooth transition feature without self-intersection in three-dimensional space.

6. The ceramic retainer according to claim 1, characterized in that: The solid lubricant, which is compositely filled inside the continuous porous skeleton, has a higher coefficient of linear thermal expansion than the ceramic matrix. The difference in their coefficients is one to two orders of magnitude, thereby enabling the supply of adaptive lubricating materials driven by differential expansion based on temperature field changes.

7. The ceramic retainer according to claim 1, characterized in that: The ceramic matrix is ​​selected from any one of silicon nitride ceramics, zirconium oxide ceramics, or silicon carbide ceramics. The solid lubricant is selected from at least one polymer material selected from polytetrafluoroethylene, polyetheretherketone, or polyimide.

8. A method for manufacturing a ceramic retainer as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1: Construct a digital model of the ceramic cage based on the three-period minimum surface implicit surface control equation with radial functional gradient porosity distribution characteristics, and reserve machining allowances for the outer cylindrical surface, inner cylindrical surface, and vertical inner wall of the pocket that require subsequent precision machining in the digital model; then, use ceramic photopolymerization 3D printing technology to stack and solidify the ceramic cage blank with radial functional gradient porosity characteristics layer by layer by controlling the layer-by-layer exposure energy and curing layer thickness. Step 2: The ceramic cage blank is placed in a debinding furnace for a multi-stage slow heating controlled step-by-step hot debinding treatment to remove the organic binder inside the blank; then the debinding blank is transferred to a high-temperature sintering furnace for densification sintering treatment to obtain a three-cycle minimum surface ceramic cage skeleton blank with a three-dimensional rigid porous network. Step 3: Using a fluid abrasive flow processing technology containing fine diamond abrasive particles, the abrasive suspension is pressurized and pushed into the porous through-flow channel of the skeleton blank, so that the abrasive suspension flows through the entire three-dimensional continuous through-flow porous network and is discharged from the outlet side. The microscopic step effect and free powder adhering to the inner wall of the channel are removed by alternating forward and reverse circulation flushing. Step 4: The skeleton blank after fluid abrasive flow treatment is placed in a vacuum impregnation chamber and evacuated to an absolute negative pressure range of 10~100Pa to remove residual air and adsorbed impurities inside the three-dimensional continuous porous network. Then, under the condition of maintaining the vacuum state, a liquid, molten or suspended solid lubricant precursor is introduced to completely immerse the skeleton blank. High-pressure gas is then introduced into the impregnation chamber to establish a positive pressure environment of 1.5~3.5MPa. Under the positive pressure, the solid lubricant precursor is forced into the internal space of the entire continuous porous skeleton. Then, in-situ solidification or cooling crystallization treatment is performed to make the volume filling density of the solid lubricant inside the porous skeleton reach 85%~95%, thus obtaining a ceramic-solid lubricant dual continuous heterogeneous composite cage blank. Step 5: Use a diamond grinding tool to perform precision mechanical grinding on the outer cylindrical surface, inner cylindrical surface, and vertical inner wall of the pocket of the composite cage blank. Remove the mechanical grinding allowance reserved in Step 1 and remove the residual solid lubricant residue on the surface. This will enable the cage to meet the predetermined mechanical dimensional accuracy and geometric tolerance requirements, and simultaneously expose the grid-like heterogeneous structure of the ceramic matrix and the solid lubricant on the friction contact surface of the pocket.

9. The preparation method according to claim 8, characterized in that: The ceramic slurry used in the ceramic photopolymerization 3D printing forming technology in step 1 is prepared by mixing photosensitive resin, dispersant, surface modifier and ceramic micro powder, and the volume solid content of the ceramic micro powder is 45%~55%.

10. The preparation method according to claim 8, characterized in that: The fluid abrasive flow processing technology in step 3 achieves graded and controllable improvement of the surface quality of the internal channels of the three-cycle minimum surface topology by programmatically adjusting the extrusion pressure of the abrasive suspension, the average particle size of the diamond abrasive, and the number of alternating forward and reverse cyclic scouring.

Citation Information

Patent Citations

  • Resin-made cage and bearing

    CN101400910A

  • A bearing cage with oil storage function

    CN110630639B

  • Polymer-metal composition retainer for self-lubricating bearing

    CN1505494A